Melha Abdullah's the Libero: A Psychoanalytic Reading (المجلة الدولية للبحوث العلمية, 2026)
Melha Abdullah is a prominent Saudi playwright and critic. Her dramatic work engages profoundly with moral, social, and cultural issues, addressing themes such as oppression, marginalization, and human struggle within restrictive environments. Although her works have attracted widespread global attention, underscoring Abdullah's role in developing Saudi theatre, feminist discourse, and audience engagement, few studies have examined her significant play, The Libero. Drawing on the psychoanalytic approach and Jung's concepts of the persona and the shadow, this study investigates how societal pressure and moral corruption contribute to psychological fragmentation. The analysis centres on the protagonist, focusing on his internal conflict and divided sense of self. This study argues that over-identification with the persona and the continued repression of the shadow lead to aggressive responses embodied in the monster Bakeleto. The findings indicate that the protagonist’s transformation represents the breakdown of the social persona under excessive moral and social strain. This collapse enables the emergence of the shadow as a psychological strategy of resistance and survival. This study offers a psychoanalytic reading of The Libero, illuminating the inner dimensions of dramatic characters in modern Saudi theatre.